Ethnobotanical study of plants with anti-tuberculosis properties from the traditional pharmacopoeia of Zuénoula, Central-Western Côte d’Ivoire - Ta, Bi Irié Honoré; Gonkeuhou, Yannick Debonheur; Piba, Serge Cherry (Ethnobotany Research and Applications, 2025)
Background: In Zuénoula, a town located to West-Central of Côte d’Ivoire, traditional medicine is often used to treat tuberculosis. However, the recipes proposed by the traditional practitioners against the disease remain a secret to the scientific community. This study exposes indigenous knowledge from traditional practitioners of Zuénoula to contribute in the search for new anti-tuberculosis recipes based on traditional medicine. Methods: A total of 87 indigenous traditional practitioners in Zuénoula were interviewed using questionnaires on plants used to combat tuberculosis. This study was carried out from August 5 to December 31, 2024. The frequency of citation of species (FCe) and Therapeutic use value (VUT) were calculated to assess the interviewees’ responses. The results were analyzed using SPSS 20 software. Results: A total of 28 plant species were indicated by the respondents as plants with anti-tuberculosis properties. The analysis of indices evaluated, showed six plants well cited and regularly exploited by the traditional practitioners of Zuénoula in the fight against tuberculosis. These are: Kleinhovia hospita (FCe = 0.09 ; VUT= 3.88), Irvingia gabonensis (FCe = 0.09 ; VUT= 3.02), Tristemma coronatum (FCe = 0.07 ; VUT= 2.95), Allium cepa (FCe = 0.06 ; VUT= 2.67), Sterculia setigera (FCe = 0.06 ; VUT= 2.04) and Persea americana (FCe = 0.06 ; VUT= 1.45). Conclusions: This study is a contribution in the search for new solutions against tuberculosis in Côte d’Ivoire and particularly in Zuénoula, a city of the country strongly affected by the disease. Keywords: Ethnobotany, Medicinal plants, Tuberculosis, Zuénoula, Côte d’Ivoire